Unveiling formative assessment in Ethiopian higher education institutions: practices and socioeconomic influences - Wondim, Mebrat Gedfie; Dessie, Behailu Atinafu (Frontiers in Education, 2025)
IntroductionFormative assessment tries to improve learning rather than simply providing judgments on learners’ achievement.ObjectiveThe purpose of the study is to examine the practice of formative assessment (FA) and the influence of socio-demographic factors (experience, education, and university category) on the practice.MethodsThe study used a quantitative research approach with a descriptive survey research design, with data collected from 319 teachers through a questionnaire designed to measure three major components of FA (feedback, alignment of FA with objectives and contents, peer, and self-assessment). To select the participants, this study used both stratified and random sampling techniques. The data analysis techniques used were both descriptive and inferential statistics.ResultsThe analysis revealed that most higher education teachers did not use formative assessment strategies to help students progress. This was shown by miss aligning FA strategies with learning objectives and contents of the course; improper feedback for learners, and lack of learners’ involvement in the assessment procedure. We did one-way ANOVA, a statistical test that reveals whether the differences we identified between groups were due to chance or were genuinely significant. The analysis noted that the level of practicing FA was found to differ significantly by university category and experience in teaching. However, ‘educational level’ yielded non-significant results on the extent of practicing FA, implying that a higher degree does not imply that a more likely to use FA strategies.Conclusions and recommendationsOverall, teachers in higher education institutions were not practicing FA strategies. Thus, universities are required to organize discussions and training that would enable teachers to recognize and discharge their multifaceted roles in performing FA.